The 1st International Electronic Conference on Horticulturae 2022
DOI: 10.3390/iecho2022-12477
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Pickled and Fresh Cucumber Slices Using Digital Image Processing and Machine Learning

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The study found that the ANN had the most accurate design in a linear function for the output layer and a hidden layer for the logistic sigmoid transfer function. Similarly, (Ropelewska et al, 2023) explored the impact of machine learning algorithms and image processing techniques to non-destructively discriminate vacuum-dried banana samples. The study found that combining all color channels after selecting image textures achieved a high accuracy of 96.89% in classifying the dried banana samples using the group of trees from the RF algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the ANN had the most accurate design in a linear function for the output layer and a hidden layer for the logistic sigmoid transfer function. Similarly, (Ropelewska et al, 2023) explored the impact of machine learning algorithms and image processing techniques to non-destructively discriminate vacuum-dried banana samples. The study found that combining all color channels after selecting image textures achieved a high accuracy of 96.89% in classifying the dried banana samples using the group of trees from the RF algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Plant leaf diseases have garnered significant attention due to their considerable effects on agriculture and daily life [10,11]. The conventional methods of disease identification are timeconsuming and prone to errors, leading to the development of innovative techniques based on deep learning.…”
Section: Introductionmentioning
confidence: 99%